2016
DOI: 10.1063/1.4962128
|View full text |Cite
|
Sign up to set email alerts
|

Properties of high-density, well-ordered, and high-energy metallic glass phase designed by pressurized quenching

Abstract: We applied gigapascal-level compressive hydrostatic pressure to the melt-quenching process of metallic glass to obtain a unique high-pressure glass state with high density that is well-ordered yet has high energy. This state contradicts the common understanding that high-density, well-ordered metallic glass states have low energy. Through molecular dynamics simulations, we found that the high-pressure glass state of the metallic glass Zr50Cu40Al10 has a rich anti-free volume and that its relaxation is dominate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Based on conventional free volume theory, the number of full icosahedra (FI) decreases in the less-relaxed state, which is usually realized by rapid cooling [ 7 , 8 ]. It is pointed that the number of full icosahedra increases with increasing pressure and the formed MG becomes denser, as expected [ 13 ]. More importantly, the atomic structure is remarkably mediated in virtue of pressure, which is identified by the Voronoi tessellation analysis.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Based on conventional free volume theory, the number of full icosahedra (FI) decreases in the less-relaxed state, which is usually realized by rapid cooling [ 7 , 8 ]. It is pointed that the number of full icosahedra increases with increasing pressure and the formed MG becomes denser, as expected [ 13 ]. More importantly, the atomic structure is remarkably mediated in virtue of pressure, which is identified by the Voronoi tessellation analysis.…”
Section: Introductionsupporting
confidence: 79%
“…It is well known that the mechanical properties of the MGs are dependent on their internal structure, which may be influenced by changing the processing history, such as using different cooling rate for MG preparation [ 5 , 6 , 7 ]. Recently, some researchers have found that MGs obtained under high hydrostatic pressure possessed a high-density, are well-ordered, and possess a high-energy metallic glass phase which contradicts the common understanding of MGs [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. While the relationship between the pressure and the internal structure is not well understood, and the mechanisms of shear band formation and propagation in pressured MGs are rarely discussed.…”
Section: Introductionmentioning
confidence: 97%
“…Previous reports have claimed the creation of a wellordered local structure but a glass in a high potential energy state was revealed by a high-pressure heat treatment in simulation 7,8 . Thus far, it has been difficult to discuss the real glassy nature of the high-pressure heat-treated alloy.…”
Section: Creation Of a New Type Of Hidden Anomalous Metallic Glassmentioning
confidence: 91%
“…The pressureinduced liquid-to-liquid transition was suggested by Dmowski et al in Zr-based metallic glasses 6 . In molecular dynamic (MD) simulation studies, polymorphic transitions and the creation of new types of abnormal glass through high-pressure heat treatment was predicted (i.e., a high-energy but high-density and well-ordered glass 7,8 ). Thus far, there have been attempts to explain these types of transitions and phenomena using many theoretical models (e.g., 4f electron delocalization 1-5 , P-and N-type free volume 8,9 , and a two-order-parameter model 10,11 ).…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] By applying pressurized quenching to a Zr-based metallic glass, a high-energy glass phase comparable to typical high-energy glass produced by rapid cooling was obtained. [12] Moreover, it is well known that structural relaxation of metallic glasses proceeds during thermal annealing processes at a temperature below the glass transition temperature 𝑇 g , which is a structural ordering process and densifies atomic packing and reconfigures the atomic structure to a low-energy state, since there is a lack of volume-generating mechanisms at high temperatures. [13,14] Relaxation usu-ally hardens and embrittles MGs, but can improve the soft magnetic properties of as-cooled Fe-based MGs.…”
mentioning
confidence: 99%